2006
DOI: 10.1597/05-070r.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Modifiers of the Palatal Phenotype in the 22q11.2 Deletion Syndrome

Abstract: Objective-To evaluate potential modifiers of the palatal phenotype in individuals with the 22q11.2 deletion syndrome.Design-Data from 356 subjects enrolled in a study of the 22q11.2 deletion syndrome were used to evaluate potential modifiers of the palatal phenotype. Specifically, subjects with and without velopharyngeal inadequacy and/or structural malformations of the palate were compared with respect to gender, race, and genotype for variants of seven genes that may influence palatal development.Methods-The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
7
1
1
Order By: Relevance
“…In summary, our analyses of these data indicate that the variation in the cardiac phenotype observed between individuals with the 22q11.2 deletion syndrome is not associated with sex, race, or five variants in four folate‐related genes. These findings are in contrast to those from previous analyses of the same study population, aimed at identifying modifiers of the palatal phenotype (Driscoll et al, 2006). Specifically, analyses of the palatal phenotype in individuals with the 22q11.2 deletion syndrome indicated that this aspect of the phenotype (i.e., the palatal phenotype) is significantly associated with both sex and race, and possibly with the MTR A2756G variant.…”
Section: Discussioncontrasting
confidence: 99%
“…In summary, our analyses of these data indicate that the variation in the cardiac phenotype observed between individuals with the 22q11.2 deletion syndrome is not associated with sex, race, or five variants in four folate‐related genes. These findings are in contrast to those from previous analyses of the same study population, aimed at identifying modifiers of the palatal phenotype (Driscoll et al, 2006). Specifically, analyses of the palatal phenotype in individuals with the 22q11.2 deletion syndrome indicated that this aspect of the phenotype (i.e., the palatal phenotype) is significantly associated with both sex and race, and possibly with the MTR A2756G variant.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to insufficient information on the rest, we cannot comment on the prevalence and degree of cognitive deficits/developmental problems. We also found a lower frequency of palatal problems in our cohort, compared to that reported in 22q11DS which is 60–70% [Driscoll et al, 2006; Ruotolo et al, 2006; Shprintzen, 2008]. However, we ascertained information regarding the palate based only on the presence or absence of structural abnormalities, specifically overt cleft or submucous cleft.…”
Section: Discussionmentioning
confidence: 41%
“…These malformations seem to be more frequent in girls and white patients with this syndrome. Along with Driscoll et al, 19 we believe that genes outside the deleted region may modify the phenotype.…”
Section: Commentsupporting
confidence: 59%
“…The phenotypic variability of this syndrome remains unexplained. According to Driscoll et al, 19 there may be a correlation with sex and ethnic origin for the occurrence of velopalatal anomalies. These malformations seem to be more frequent in girls and white patients with this syndrome.…”
Section: Commentmentioning
confidence: 99%